2019
DOI: 10.1016/j.jfda.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro α-amylase and pancreatic lipase inhibitory activity of Cornus mas L. and Cornus alba L. fruit extracts

Abstract: Less-common fruits from Cornus spp. (Cornaceae), also named dogwoods, have shown antidiabetic, antibacterial and anti-allergic properties and are thus considered a source of phytochemicals that are beneficial to human health. The study aimed to compare the chemical compositions of the aqueous and ethanolic extracts of lyophilized fresh-picked and commercially available dried fruits of Cornus mas (Cm, cornelian cherry) and Cornus alba (Ca) fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…Firstly, the total phenols content was determined. Among all studied extracts, the highest content of phenolic compounds was found in the aqueous-ethanolic extract from the fruits of CA (39.60 ± 2.28 mg GAE/g of extract) as it was described in our previous study [13]. The content of phenolic compounds expressed as gallic acid equivalent in extract from fruits of CF was determined for the first time (24.30 ± 1.72 mg GAE/g).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Firstly, the total phenols content was determined. Among all studied extracts, the highest content of phenolic compounds was found in the aqueous-ethanolic extract from the fruits of CA (39.60 ± 2.28 mg GAE/g of extract) as it was described in our previous study [13]. The content of phenolic compounds expressed as gallic acid equivalent in extract from fruits of CF was determined for the first time (24.30 ± 1.72 mg GAE/g).…”
Section: Discussionsupporting
confidence: 62%
“…Taking into consideration all the results obtained both in this and our previous study [13], it was concluded that the aqueous-ethanolic extract from fruits of CA was the most active one. In order to find the phytochemicals responsible for this activity, the isolation of compounds from acetone-methanol-water extract (3:1:1, v/v/v) was carried out.…”
Section: Digestive Enzymes Inhibitionsupporting
confidence: 55%
See 3 more Smart Citations